A inserção da temática meio ambiente nos cursos de licenciatura do IFMG: análise das possibilidades a partir dos projetos políticos pedagógicos e da visão dos coordenadores - Pereira, Cláudio Alves (2016)
In this research the objective was to investigate the insertion of the Environment theme licentiate1 courses of the Federal Institute of Education, Science and Technology of Minas Gerais (IFMG) in teaching, research and extension activities, in order to contribute to eco-citizenship background to its students. Eight licentiate courses offered in 2016, distributed in six campus of the institution were taken as reference. The research methodology, based on a qualitative approach, is based on three strategies: in the documents analysis that guide these courses, in the accomplishment of open interviews with their coordinators and in the information crossing collected with the notes of theoretical references. With these three analyzes, we tried to evidence signs of the proposition and practice of the work with the Environment theme in the courses analyzed. Data analysis and categorizations are based on Bardin (2009). The relevance of this research lies in the necessary discussion about how licentiate courses have been working on the Environment theme, in a process of analysis that goes beyond the formal compliance with the legislation and believes that this is an essential issue, a right of every citizen in his/her integral formation process and, in addition, in his/her process of eco-citizen formation. The data analysis indicates that there is no single way to be followed, a recipe ready to carry out the educational work with the environmental theme, but that although some courses do not do, it is possible to include the Environment theme in the curriculum of the licentiate courses independently the area. It could be noticed that a management commitment is necessary, both at institutional and local level, so that the theme leaves the official documents and reaches to the learning spaces inside the institutes. The analysis also pointed out that work with the Environment theme should go beyond the proposal for inclusion of a subject in the curriculum of the course, but should be planned to involve teaching, research and extension projects. The IFMG licentiate courses were taken as a reference, but the results can be studied for other education’s institutions also offer the same modality courses and, thus, it can contribute to the necessary debate to the licentiate’s students be guaranteed a background that allow to assume the important social role of articulating the work with environmental theme in educational institutions, especially in basic education.